Osteosarcoma – a rare clinical presentation and management approach - Talwar, Aarti; Sharma, Tarun; Kamarathi, Nagaraju; Goel, Sumit; Sindhu, Simran Jeet; Singh, Supriya (International Journal of Basic & Clinical Pharmacology, 2025)
Osteosarcomas arise from primitive mesenchymal cells, primarily originating in bone and rarely in soft tissue. If left untreated, they follow an aggressive course, leading to local and metastatic disease progression. Osteosarcoma is an uncommon type of sarcoma characterized by the histological presence of osteoid production linked to malignant mesenchymal cells. It is the third most prevalent cancer in children and adolescents, following lymphomas and brain tumors. The exact causes remain unclear, but its occurrence in the growing population and its typical location at the ends of long bones suggest a link to rapid bone production.